Alterations in evertor/invertor muscle activation and center of pressure trajectory in participants with functional ankle instability - Ty Hopkins, J.; Coglianese, Mark; Glasgow, Philip; Reese, Shane; Seeley, Matthew K. (Journal of electromyography and kinesiology, 2012)
Participants with ankle instability demonstrate more foot inversion during the stance phase of gait than able-bodied subjects. Invertor excitation, coupled with evertor inhibition may contribute to this potentially injurious position. The purpose of this experiment was to examine evertor/invertor muscle activation and foot COP trajectory during walking in participants with functional ankle instability (FI). Twelve subjects were identified with FI and matched to healthy controls. Tibialis anterior (TA) and peroneus longus (PL) electromyography (EMG), as well as COP, were recorded during walking. Functional analyses were used to detect differences between FI and control subjects with respect to normalized EMG and COP trajectory during walking. Relative to matched controls, COP trajectory was more laterally deviated in the FI group from 20% to 90% of the stance phase. TA activation was greater in the FI group from 15% to 30% and 45% to 70% of stance. PL activation was greater in the FI group at initial heel contact and toe off and trended lower from 20% to 40% of stance in the FI group. Altered motor strategies appear to contribute to COP deviations in FI participants and may increase the susceptibility to repeated ankle inversion injury.